Film for removing electrode material and method for removing electrode material
Patent Information
- Application Number
- JP2025059771
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0017】 本発明によれば、使用済み二次電池の電極から、電極材料を効率的に剥離し、回収するための電極材料剥離用フィルム、および電極材料の剥離方法を提供できる。
Smart Images

Figure 2026166674000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to recycling of electrode materials from spent secondary batteries, and more particularly relates to a peeling film and a peeling method for peeling an active material layer from a current collector constituting the electrode material.
Background Art
[0002] In recent years, recycling of spent secondary batteries has attracted attention. Among them, for spent lithium-ion batteries containing rare metals such as NCA, recycling processes that burn the spent batteries themselves and extract rare metals from the remaining metals have been studied (for example, see Patent Document 1).
[0003] However, for lithium iron phosphate that does not contain rare metals, such recycling processes are not cost-effective. Conventionally, in the recycling of spent lithium iron phosphate (hereinafter referred to as "LFP") batteries, lithium contained in LFP is extracted and reused, but other iron sources and phosphorus sources have been discarded. However, at present, in the technology of taking out the positive electrode from a spent LFP battery and separating and regenerating the positive electrode material on the surface of the positive electrode, although there are positive electrode material separation methods such as the electric pulse method, there are various problems such as large-sized equipment, low processing capacity, and the aluminum foil as the current collector is destroyed during the separation treatment and mixes into the recovered positive electrode active material.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0005] The present invention has been made in view of the above problems, and provides an electrode material peeling film and an electrode material peeling method for efficiently peeling and recovering electrode material from the electrodes of used secondary batteries. [Means for solving the problem]
[0006] In other words, according to one aspect of the present invention for solving the above problems, the first aspect of the present invention is a film for releasing electrode materials, comprising a water-soluble, irritation-curing adhesive layer on the surface of a base film.
[0007] A second aspect of the present invention is a film for releasing electrode materials in which the water-soluble stimulus-curing adhesive layer in the first aspect is a water-soluble ultraviolet-curing adhesive layer.
[0008] A third aspect of the present invention is an electrode material release film in which the cured film thickness of the water-soluble stimulus-curing adhesive layer in the first aspect is 1 μm or more and 20 μm or less.
[0009] A fourth aspect of the present invention is, in the second aspect, a film for peeling off electrode materials having an ultraviolet irradiation transmittance of 85% or more at a wavelength of 365 nm.
[0010] A fifth aspect of the present invention is an electrode material peeling film in the first aspect, wherein the conditions for peeling the water-soluble stimulus-curing adhesive layer from the surface of the substrate film in water with a water temperature of 10°C to 60°C are the addition of ultrasound with a wavelength of 28 Hz to 120 Hz.
[0011] A sixth aspect of the present invention is an electrode material release film in which the thickness of the base film in the first aspect is 10 μm or more and 300 μm or less.
[0012] A seventh aspect of the present invention is an electrode material release film in which the electrode material in the first aspect is the positive electrode material.
[0013] An eighth aspect of the present invention is an electrode material release film in which the electrode material in the first aspect is the negative electrode material.
[0014] A ninth aspect of the present invention is a method for peeling off an electrode material, comprising the steps of: laminating an adhesive film onto the surface of the active material layer of an electrode material comprising a metal layer and an active material layer, thereby bonding the surface of the active material layer to the film; and peeling the active material layer that has been bonded to the film from the metal layer.
[0015] A tenth aspect of the present invention is a method for stripping an electrode material, characterized in that the electrode material in the ninth aspect is a positive electrode material, wherein the metal layer contains aluminum and the active material layer contains lithium iron phosphate.
[0016] An eleventh aspect of the present invention is a method for stripping an electrode material, characterized in that the electrode material in the ninth aspect is a negative electrode material, wherein the metal layer contains copper and the active material layer contains carbon and a binder. [Effects of the Invention]
[0017] According to the present invention, it is possible to provide an electrode material peeling film and an electrode material peeling method for efficiently peeling and recovering electrode material from the electrodes of used secondary batteries. [Brief explanation of the drawing]
[0018] [Figure 1] This is a cross-sectional diagram of the electrode material. [Figure 2] This is a cross-sectional diagram of the electrode material release film according to the present invention. [Figure 3] This is an explanatory diagram of an electrode material peeling apparatus according to the present invention. [Modes for carrying out the invention]
[0019] Here, the method for peeling an electrode material of the present invention has as its technical concept a method for peeling an electrode material, comprising: a step of bonding an adhesive film to the surface of the active material layer of a positive electrode material or a negative electrode material, which is an electrode material composed of a metal layer and an active material layer, to adhere the surface of the active material layer to the film; and a step of peeling the active material layer adhered to the film from the metal layer.
[0020] An example of the electrode material of the present invention is shown in Figure 1. In Figure 1, reference numeral 1 denotes an electrode material, which has a configuration including an active material layer 12 on one or both sides of a metal layer 11. Here, the metal layer 11 functions as a current collector in a secondary battery, and an aluminum foil or a copper foil is usually used therefor. Here, the electrode material in the present specification includes not only a positive electrode material composed of a lithium nickel cobalt manganese composite oxide or lithium iron phosphate as a positive electrode active material, a binder, a conductive auxiliary agent and the like, but also a negative electrode material composed of a negative electrode active material (for example, carbon), a binder, a conductive auxiliary agent and the like. That is, not only the peeling method for a positive electrode material but also the peeling method for a negative electrode material are included within the scope of the present invention. More specifically, as described in the following examples, the present invention is not limited to the case where the metal layer in the positive electrode material is an aluminum foil and the active material thereof is lithium iron phosphate, and the metal layer in the negative electrode material layer may be a copper foil and the active material thereof may be made of carbon.
[0021] Figure 2 is a cross-sectional configuration diagram of the film 2 for peeling an electrode material used in the peeling method according to the present invention. The film 2 for peeling an electrode material according to the present invention is a water-soluble film having both stimulus curability and adhesiveness, and as one configuration thereof, the film is provided with a water-soluble stimulus-curable adhesive layer 21 having both stimulus curability and adhesiveness on a base film 20, and a material that exhibits its effect by radiation such as ultraviolet rays or heat (temperature) is used as the stimulus source. A product in which the base film 20 and the water-soluble stimulus-curable adhesive layer 21 are integrated can also be used. While radiation such as ultraviolet light, heat (temperature), and pressure can be used as stimuli for the water-soluble stimulus-curing adhesive layer 21, it is preferable to use a water-soluble ultraviolet-curing adhesive layer from the viewpoint of ease of handling.
[0022] As the base film 20, films made of PET or acrylic resin, or films made of paper or synthetic fibers can be used, but it is preferable to use a PET film from the viewpoint of ultraviolet light transmission.
[0023] The water-soluble UV-curable adhesive layer 21 hardens when exposed to UV light, exhibiting its adhesive properties and enabling easy peeling at the interface between the metal layer 11 and the active material layer 12.
[0024] Next, the peeling method according to the present invention will be explained using Figure 3. In Figure 3, reference numeral 30 denotes the peeling device used, 31 is a pressure roller, 32 is a transfer roll, 33 is a conveyor roll, 34 is an unwinding roll, 35 is a winding roll, 36 is a scraper, 37 is a collection container, and 38 is a separation roll. First, prepare an electrode material release film 2 equipped with the water-soluble, irritation-curing adhesive layer 21 described above. Furthermore, a water-soluble UV-curable adhesive layer was used as the water-soluble irritation-curing adhesive layer 21. Next, the water-soluble UV-curable adhesive layer 21 of the electrode material release film 2 is bonded to the active material layer 12 on the surface of the electrode material 1 taken from the used secondary battery, and pressure is applied with a pressure roller 31. This causes the active material layer 12 and the water-soluble UV-curable adhesive layer 21 on the surface of the electrode material release film 2 to adhere tightly.
[0025] Subsequently, ultraviolet irradiation is performed using an ultraviolet irradiation device (not shown) to activate the adhesive effect of the water-soluble ultraviolet-curable adhesive layer 21, causing the electrode material release film 2 and the surface of the active material layer 12 to adhere, making it possible to peel the active material layer 12 from the interface with the metal layer (aluminum foil) 11. In one embodiment of the present invention, the active material layer 12 adhered to the electrode material release film 2 is peeled off from the metal layer (aluminum foil) 11, starting from the contact area with the transfer roll 32. In other words, the active material layer 12 is transferred from the electrode material 1 to the electrode material release film 2, starting from the contact area with the transfer roll 32.
[0026] The electrode material release film 2, onto which the active material layer 12 has been transferred, is transported by a transport roll 33 and a winding roll 35, immersed in water, and subjected to ultrasonic irradiation by an ultrasonic irradiator (not shown) to dissolve the water-soluble ultraviolet-curable adhesive layer 21. The active material layer 12 is then separated from the battery electrode material release film 2 by a separation roll 38 and a scraper 36. The separated active material layer 12 is collected in a recovery container 37. In the case of a configuration in which an active material layer 12 is provided on both sides of a metal layer (aluminum foil) 11, as shown in the explanatory diagram in Figure 3, by adhering the electrode material peeling film 2 to both sides of the active material layer 12 of the electrode material 1, the active material layers 12 on both sides can be peeled off and collected in the recovery container 37.
[0027] According to the peeling method of the present invention, the active material layer can be peeled from the metal layer, regardless of whether it is a positive electrode material or a negative electrode material.
[0028] Furthermore, the peeling method of the present invention prevents metal foils such as aluminum, which are generated during the electrode material separation process from the current collector using conventional methods such as electric pulse methods, from being mixed into the recovered active material. Moreover, since the processing apparatus itself is relatively simple, it consumes little power, is highly safe, and is cost-effective.
[0029] Here, the cured film thickness of the water-soluble, irritation-curing adhesive layer is preferably 1 μm to 20 μm. From the viewpoint of adhesion, the cured film thickness of the adhesive layer is preferably 1 μm or more. Furthermore, from the viewpoint of peelability, the cured film thickness of the adhesive layer is preferably 20 μm or less.
[0030] Furthermore, it is preferable that the transmittance of the electrode material release film at a wavelength of 365 nm be 85% or higher. By setting the transmittance to 85% or higher, sufficient ultraviolet irradiation is performed on the water-soluble ultraviolet-curable adhesive layer, and the adhesive effect is fully realized. As a result, peeling at the interface between the metal layer and the active material layer is improved.
[0031] The conditions for peeling the water-soluble stimulus-curing adhesive layer from the surface of the substrate film in water with a temperature of 10°C to 60°C are preferably those involving the application of ultrasound at a wavelength of 28 Hz to 120 Hz. From the viewpoint of the solubility of the adhesive layer, a wavelength of 28 Hz or higher is preferable. Furthermore, by setting the wavelength to 120 Hz or lower, partial dissolution of the adhesive layer can be prevented.
[0032] The thickness of the base film is preferably 10 μm or more and 300 μm or less. From the viewpoint of preventing film breakage during peeling, the thickness of the base film is preferably 10 μm or more. Furthermore, from the viewpoint of preventing peeling defects, the thickness of the base film is preferably 300 μm or less. [Examples]
[0033] The following describes in detail, with reference to an embodiment of the present invention, a film for peeling electrode materials and a peeling method using the film, but the present invention is not limited to these embodiments. [Examples]
[0034] [Preparation of electrode material release film 2] A water-soluble UV-curing adhesive (Kyōritsu Chemical Industry Co., Ltd., Water-soluble Type 3200) was applied to the easily bonded surface of a 38 μm thick PET film (Mitsubishi Chemical Corporation, product name: Diafoil T-600E) using a bar coater to achieve a cured film thickness of 2 μm, and then dried at 100°C.
[0035] [Bonding with positive electrode material 1 and peeling off active material layer 12] The positive electrode material 1 was bonded to the side of the electrode material release film 2 prepared above, which had a water-soluble ultraviolet-curable adhesive layer 21, so that the active material layer 12 was in contact with it, and the bonding was performed using a roll-type bonding device to prevent air from being trapped. Next, ultraviolet light (365nm wavelength, irradiation dose: 500mJ / cm²) is irradiated from the substrate film 20 side of the electrode material release film 2 using an ultraviolet irradiation device. 2 After performing the above, the positive electrode material 1 and the electrode material release film 2 were separated using the contact area with the transfer roll 32 as a starting point, thereby transferring the active material layer 12 to the electrode material release film 2 side.
[0036] The electrode material release film 2, onto which the active material layer 12 was transferred, was further transported by a transport roll 33 and a winding roll 35, immersed in water, and irradiated with ultrasound (40 kHz) at a water temperature of 25°C for 3 minutes using an ultrasonic irradiation device to dissolve the water-soluble ultraviolet-curable adhesive layer 21 in water. Then, the active material layer 12 was separated from the electrode material release film 2 using a separation roll 38 and a scraper 36. The separated active material layer 12 was collected in a recovery container 37.
[0037] [Treatment of the active material layer 12] The active material layer 12, separated from the electrode material release film 2, was separated from water using a filter and dried at 100°C for 24 hours. Subsequently, it was heated at 400°C to incinerate the binder contained in the active material layer, thereby obtaining lithium iron phosphate powder.
[0038] [Battery evaluation] Using the lithium iron phosphate obtained by the above procedure, a coin cell was fabricated and its performance (charge / discharge evaluation) was performed. [Examples]
[0039] The procedure was the same as in Example 1, except that the preparation of the electrode material peeling film 2, the bonding with the positive electrode material 1, and the peeling of the active material layer 12 were modified as follows. [Preparation of electrode material release film 2] A water-soluble UV-curing adhesive (TESC Co., Ltd. Water-Soluble Peel Type A-1134D) was applied to the easily bonded surface of a 38 μm thick PET film (Mitsubishi Chemical Corporation, product name: Dia Foil T-600E) using a bar coater to achieve a cured film thickness of 2 μm, and then dried at 100°C.
[0040] [Bonding with positive electrode material 1 and peeling off active material layer 12] Ultraviolet irradiation was performed at a wavelength of 365 nm, with an irradiation dose of 1000 mJ / cm². 2 That's what I decided. [Examples]
[0041] The preparation of the electrode material peeling film 2 was carried out in the same manner as in Example 1, except that the following modifications were made. [Preparation of electrode material release film 2] A water-soluble UV-curing adhesive (Kyōritsu Chemical Industry Co., Ltd., Water-soluble Type 3200) was applied to the easily bonded surface of a 38 μm thick PET film (Mitsubishi Chemical Corporation, product name: Diafoil T-600E) using a bar coater, so that the cured film thickness would be 1 μm, and then dried at 100°C. [Examples]
[0042] The preparation of the electrode material peeling film 2 was carried out in the same manner as in Example 1, except that the following modifications were made. [Preparation of electrode material release film 2] A water-soluble UV-curing adhesive (Kyōritsu Chemical Industry Co., Ltd., Water-soluble Type 3200) was applied to the easily bonded surface of a 38 μm thick PET film (Mitsubishi Chemical Corporation, product name: Dia Foil T-600E) using a bar coater to achieve a cured film thickness of 20 μm, and then dried at 100°C. [Examples]
[0043] The procedure was carried out in the same manner as in Example 1, except that the bonding with the positive electrode material 1 and the peeling of the active material layer 12 were modified as follows. [Bonding with positive electrode material 1 and peeling off active material layer 12] Ultrasonic irradiation was performed for 3 minutes at a water temperature of 10°C (40kHz). [Examples]
[0044] The procedure was carried out in the same manner as in Example 1, except that the bonding with the positive electrode material 1 and the peeling of the active material layer 12 were modified as follows. [Bonding with positive electrode material 1 and peeling off active material layer 12] Ultrasonic irradiation was performed at a water temperature of 60°C for 3 minutes (40kHz). [Examples]
[0045] The procedure was carried out in the same manner as in Example 1, except that the bonding with the positive electrode material 1 and the peeling of the active material layer 12 were modified as follows. [Bonding with positive electrode material 1 and peeling off active material layer 12] Ultrasonic irradiation was performed at a water temperature of 25°C for 3 minutes (28kHz). [Examples]
[0046] The procedure was carried out in the same manner as in Example 1, except that the bonding with the positive electrode material 1 and the peeling of the active material layer 12 were modified as follows. [Bonding with positive electrode material 1 and peeling off active material layer 12] Ultrasonic irradiation was performed for 3 minutes (120kHz) at a water temperature of 25°C. [Examples]
[0047] The preparation of the electrode material peeling film 2 was carried out in the same manner as in Example 1, except that the following modifications were made. [Preparation of electrode material release film 2] A water-soluble UV-curing adhesive (Kyōritsu Chemical Industry Co., Ltd., water-soluble type 3200) was prepared by mixing 10 wt% silica (primary particle size: 50 nm). This adhesive was applied to the easily bonded surface of a 38 μm thick PET film (Mitsubishi Chemical Corporation, product name: Dia Foil T-600E) using a bar coater to achieve a cured film thickness of 2 μm, and then dried at 100°C. [Examples]
[0048] The preparation of the electrode material peeling film 2 was carried out in the same manner as in Example 1, except that the following modifications were made. [Preparation of electrode material release film 2] A water-soluble UV-curing adhesive (Kyōritsu Chemical Industry Co., Ltd., Water-soluble Type 3200) was applied to the easily bonded surface of a 12 μm thick PET film (Mitsubishi Chemical Corporation, product name: Diafoil T-600E) using a bar coater to achieve a cured film thickness of 2 μm, and then dried at 100°C.
[0049] [Fabrication of lithium iron phosphate batteries] [Fabrication of the positive electrode] The lithium iron phosphate obtained in the example, acetylene black (AB) as a conductive additive, and polyvinylidene fluoride (PVdF) as a binder were mixed with N-methyl-2-pyrrolidinone (NMP) in a mass ratio of electrode material:AB:PVdF = 90:5:5 to form a positive electrode composite paste. The resulting paste was applied to a 30 μm thick aluminum foil, dried, and then pressed together using a roll press with a press spacing of 30 μm to form an electrode plate.
[0050] [Battery construction] The resulting electrode plates are punched out in a circular punching machine, with an area of 2 cm². 2 The material was punched out in a circular shape, dried in a vacuum dryer at 60°C for 15 hours, and then a coin cell of a lithium iron phosphate battery, with lithium as the negative electrode, was fabricated in a glove box.
[0051] [Battery Evaluation (Charge / Discharge Evaluation)] The charge capacity of the obtained coin cells was measured when charged at 25°C at a rate of 0.1C, and the discharge capacity was measured when discharged at 0.1C. The results are shown in the "Charge Capacity" and "Discharge Capacity" columns of Table 1.
[0052] The results obtained for Examples 1 to 10 are shown in Table 1.
[0053] [Table 1]
[0054] [evaluation] In all of the electrode material release films in Examples 1 to 10, it was confirmed that the release properties were good when the active material layer of the positive electrode material was peeled off and transferred to the electrode material release film side. Furthermore, the evaluation (charge / discharge capacity) of coin cells made from lithium iron phosphate recovered using the electrode material peeling films of Examples 1 to 10 was confirmed to be sufficient in all cases. [Explanation of Symbols]
[0055] 1 Electrode material 2. Film for releasing electrode material 11. Metal layer (aluminum foil) 12 Active material layer 20 Base film 21 Water-soluble stimulation (ultraviolet) curable adhesive layer 30 Peeling device 31 Pressure Roller 32 Transfer Rolls 33 Conveyor Rolls 34 unwinding rolls 35 reel rolls 36 Scrapers 37 Collection containers 38 Separation Rolls
Claims
1. A film for releasing electrode materials, characterized by having a water-soluble, irritation-curing adhesive layer on the surface of a base film.
2. The electrode material release film according to claim 1, characterized in that the water-soluble irritation-curing adhesive layer is a water-soluble ultraviolet-curing adhesive layer.
3. The electrode material release film according to claim 1, characterized in that the film thickness of the water-soluble stimulus-curing adhesive layer after curing is 1 μm or more and 20 μm or less.
4. The electrode material release film according to claim 2, characterized in that the transmittance of ultraviolet irradiation at a wavelength of 365 nm is 85% or more.
5. The electrode material peeling film according to claim 1, characterized in that the conditions for peeling the water-soluble stimulus-curing adhesive layer from the surface of the substrate film in water with a water temperature of 10°C to 60°C are the application of ultrasound with a wavelength of 28 Hz to 120 Hz.
6. The electrode material release film according to claim 1, characterized in that the thickness of the base film is 10 μm or more and 300 μm or less.
7. The electrode material release film according to claim 1, characterized in that the electrode material is a positive electrode material.
8. The electrode material release film according to claim 1, characterized in that the electrode material is a negative electrode material.
9. A step of bonding an adhesive film to the surface of the active material layer of an electrode material including a metal layer and an active material layer, thereby bonding the surface of the active material layer and the film, A method for peeling off an electrode material, characterized by comprising the step of peeling off the active material layer adhered to the film from the metal layer.
10. The electrode material is a positive electrode material, The method for peeling off an electrode material according to claim 9, characterized in that the metal layer contains aluminum and the active material layer contains lithium iron phosphate.
11. The electrode material is a negative electrode material, The method for stripping an electrode material according to claim 9, characterized in that the metal layer contains copper and the active material layer contains carbon and a binder.
Citation Information
Patent Citations
Storage battery recycling method
JP2023086494A